2002
DOI: 10.2134/agronj2002.0072
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × Environment Interactions and Yield Stability of Food-Grade Soybean Genotypes

Abstract: both in the national and international markets (Carter and Wilson, 1998;Boerma and Mian, 1998). Soyfoods Soybean [Glycine max (L.) Merr.], an important component of have been reported to provide protection against heart the Asian diet, is gaining popularity as a source of vegetable protein and phytochemicals in the USA. However, soybean cultivars with disease, cancer, menopausal symptoms, and other disdesirable agronomic traits and biochemical components that enhance eases (Carter and Wilson, 1998; Messina an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 14 publications
(27 reference statements)
3
47
0
2
Order By: Relevance
“…This Harvest Index range fell within the range (i.e. 0.37-0.45) reported by Rao et al (2002) and that reported by Spaeth et al (1984; Harvest Index range 0.25-0.6)). The estimated average root:shoot ratio soybean at harvest was 0.18.…”
Section: Sibcrop Simulations For Summer Crops (Maize and Soybean)supporting
confidence: 82%
See 1 more Smart Citation
“…This Harvest Index range fell within the range (i.e. 0.37-0.45) reported by Rao et al (2002) and that reported by Spaeth et al (1984; Harvest Index range 0.25-0.6)). The estimated average root:shoot ratio soybean at harvest was 0.18.…”
Section: Sibcrop Simulations For Summer Crops (Maize and Soybean)supporting
confidence: 82%
“…Although certain croplands may physically resemble grasslands (i.e. compared to forests), they differ substantially in terms of seasonality, phenology and physiology, and harvested products, which can account for 40-60% of the above ground biomass (Hay, 1995;Prince et al, 2001;Rao et al, 2002;Heard, 2004) that is exported after the crop reaches maturity. Therefore models that simulate agricultural ecosystems should have a good representation of the crop phenology and physiology that are associated with the unique properties of these ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…In relation to interaction between sowing date and cultivar, Rao et al (2002) cited that different environments influenced mass of 100 seeds, but, the genotypes had more influence. De Bruin and Pedersen (2008) verified in their study, one determined growth habit cultivar that practically did not alter its mass of 100 seeds, at different sowing dates or plant spacing, similarly to cultivar BRS 284 in this study, showing the importance of genotype stability.…”
Section: Discussionmentioning
confidence: 99%
“…There is a need to introduce, evaluate, and characterise vegetable soybean cultivars of domestic and Asian origins for cultivation in the United States. Development of soybean cultivars for vegetable purposes offers potential for expanding the domestic and international soybean markets (Rao et al 2000).…”
Section: Introductionmentioning
confidence: 99%